2021
DOI: 10.3390/plants10091966
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of Medicinal Plants Used Traditionally to Manage Kidney Diseases in North-Eastern Morocco: Ethnobotanical Fieldwork and Pharmacological Evidence

Abstract: Kidney disease is one of the most common health problems and kidney failure can be fatal. It is one of the health disorders associated with extreme pain and discomfort in patients. In developing countries, such as Morocco where socioeconomic and sanitary conditions are precarious, medicinal plants are considered the primary source of medication. In the present work an ethnobotanical survey was conducted in a remote area of North-Eastern Morocco and we focused on (1) establishing a record of medicinal plants us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(45 citation statements)
references
References 148 publications
5
40
0
Order By: Relevance
“…Furthermore, trans-GMCA, GMPPA as well as 4,4 -dimethoxy-2,2 -di-O-hexoside-truxinate were previously identified in n-butanol fraction from aerial parts of Lavandula angustifolia Mill. [19] HIh-PE contained a variety of 3-hydroxy-3-methylglutaric (HMG) acid conjugates with quercetin (peak 22), 7-O-methylquercetin (peak 31), kaempferol (peaks 24, 28), and 7-Omethylkaempferol (peaks [33][34][35][36][37]. Three non-phenolic metabolites: maltol derivative (LB), N-malonyl-tryptophan (peak 14), and a trace amount of blumenin isomer (peak 23) were also identified in these extracts.…”
Section: Phytochemical Profiles and The Content Of Individual Phenoli...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, trans-GMCA, GMPPA as well as 4,4 -dimethoxy-2,2 -di-O-hexoside-truxinate were previously identified in n-butanol fraction from aerial parts of Lavandula angustifolia Mill. [19] HIh-PE contained a variety of 3-hydroxy-3-methylglutaric (HMG) acid conjugates with quercetin (peak 22), 7-O-methylquercetin (peak 31), kaempferol (peaks 24, 28), and 7-Omethylkaempferol (peaks [33][34][35][36][37]. Three non-phenolic metabolites: maltol derivative (LB), N-malonyl-tryptophan (peak 14), and a trace amount of blumenin isomer (peak 23) were also identified in these extracts.…”
Section: Phytochemical Profiles and The Content Of Individual Phenoli...mentioning
confidence: 99%
“…Despite the presence in traditional medicine and contemporary herbal therapies, molecular mechanisms and main pathways of biological actions of Herniaria species are poorly recognized. So far, only some aspects of the biological actions of H. glabra and H. hirsuta L. have been described [32,33]. While the most of studies on H. glabra are focused on its diuretic [34] and anti-urolithiasis activity [35], other biological actions of different Herniaria species remain inadequately recognized.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…In vitro study showed that flavonoids extracted from C. reticulata has strong anti-collagenase and anti-elastase potential [87]. In Morocco, according to Bencheikh et al, Citrus species (lemon, lime, age-leaved rock-rose and sweet orange) are widely used in the treatment of renal problems, including renal stones, colic and insufficiency [88]. Murata et al showed both hesperetin and naringenin extracted from Citrus fruits had anti-allergic effects on rat basophil leukemia RBL-2H3 cells.…”
Section: Other Biological Effectsmentioning
confidence: 99%
“…AMPs play a crucial and fundamental role in traditional medicine and play a very significant role in drug discovery [1]. Natural substances account for around 25% of all medicines available for the treatment of illnesses (plants, animals, bacteria, and fungi) [2]. Cistus ladanifer L. is one of the medicinal plants, belonging to the Cistaceae family, the latter represented by seven genera (Cistus, Fumane, Halimium, Tuberaria, Helianthemum, Hudsonia and Lechea), the genus Cistus alone encompass 16 species particularly distributed in the Mediterranean region [3,4], this kind is widespread in Portugal, Spain, Italy, Algeria, and Morocco [5].…”
Section: Introductionmentioning
confidence: 99%